Influencing Factors of Non-STEM Students Shifting to STEM-related College Programs in a Catholic University - Gaviola, Andre Louis (Animo Repository, 2023)
The additional two years in the Senior High School curriculum allow the student to select a specialization depending on ability, interests, and academic capabilities that will prepare them for their chosen course in college. However, statistics show that more students shift from their chosen strand in Senior High School when they pursue their undergraduate education. Thus, this study was conducted to determine the degree of influence of factors affecting the shift of non-STEM students to STEM-related courses. This quantitative research utilized the descriptive and comparative research approaches. The data were gathered from the randomly selected 214 college students of STEM-related college programs who are shiftees from the non-STEM strand in Senior High School. Using mean and standard deviation, results showed that work opportunities are the most dominant influencing factor in the shift of non-STEM students to STEM-related college programs. Further, utilizing the Mann-Whitney U test and when grouped according to sex, the result showed no significant difference in the degree of influencing factors to shift career choice. Using the Kruskal-Wallis H Test and when grouped according to strand in Senior High School, the result showed no significant difference in the degree of influencing factors to shift career choice. A career awareness seminar was developed based on the findings of the study.